(untitled) (Research, Society and Development, 2022)
The Caparaó microregion is one of the microregions of the Brazilian state of Espírito Santo. Its name refers to the mountain of the same name, which is part of the Caparaó National Park. Through a systemic approach, we aim to understand the transformations and dynamics of the region’s agrarian systems. Data were obtained by bibliographic review, documental research and observation and coexistence with family farming. We perform content analysis and data triangulation. Regarding regional zoning, we highlighted climate, relief, hydrography and vegetation. We divided the timeline into four agrarian systems: Indigenous, Immigrants, Small Property and Modern Coffee. GDP and HDI data still need improvement. Much of this, we believe, is linked to the extermination of indigenous people and the enslavement of people, a scenario seen in the first two systems. Serra do Caparaó is part of the territory that is very important for the dynamism of the landscapes and, therefore, of the agrarian systems. Such a mountain range makes possible two well-marked climatic seasons, high altitudes and undulating relief; in addition to feeding important hydrographic basins and offering adequate agronomic conditions for the cultivation of coffee, the main crop in the region. Despite having been much explored in the Small Property Agrarian System, its territory is still today an important fragment of Atlantic Forest, despite being essentially isolated by coffee plantations. This insular situation was consolidated in the Modern Coffee Culture Agrarian System, strongly encompassed by the green revolution. Its diversity has diminished. Despite this, we point out some situations that differ from monoculture, such as rural tourism and the production of specialty coffees.